Pengembangan Media Belajar Pembagian Melalui Papan Pintar Fun Math untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa SDN Pekayon 16 Pagi - Katharina Stefania Ade Jaro; Yuniarti Yuningsih; Aura Anastria Putri; Jessica Laura Septiana Hutagalung; Tiara Dwitarakanita (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
This research aims to develop an interactive learning medium that can enhance students' conceptual understanding of mathematics, specifically in division, through the use of the Fun Math Smart Board. The method used is Research and Development (R&D) which includes the stages of needs analysis, design, development, and product evaluation. The data collection techniques were conducted through pretest, posttest, observation, and interviews with the research subjects being elementary school students selected purposively. The results of the study show that the use of the interactive learning medium Fun Math Smart Board significantly improved students' understanding of division concepts by 87%. This medium facilitates students' comprehension through visualization and interaction. Additionally, its use increases students' interest and participation in the learning process. This study concludes that the Fun Math Smart Board is an effective learning medium for strengthening students' mathematical conceptual understanding, particularly in division. These findings are expected to serve as a reference for teachers in developing innovative and interactive learning media.